63‐3: The Novel FFS Structure to Improve Image‐Sticking in Liquid Crystal Displays. Issue 1 (May 2016) - Woo, ChangSeung; Hong, SoonHwan; Oh, DaeSeok; Chung, MoonSoo; Kim, HyoungSik; Nam, Yousung; Lee, JuYoung; Jun, MyungChul; Kang, InByeong
Abstract : Image‐Sticking in Liquid Crystal Displays (LCDs) was found to be dependent on the accumulation of ionic charges at interface between liquid crystal (LC) and alignment layer through the residual voltage bias after the driving waveforms. In the case of the Fringe Field Switching (FFS) structure, it can be weaker to Image‐Sticking because the only one polarity electrode is located on the top of TFT glass. In this paper, we investigate the novel FFS structure to improve Image‐Sticking. The proposed structure of FFS has a form of exposing the pixel electrode and common electrode at the same time, can be made by applying the dry etch process without additional patterning process. As a result, two electrodes are in contact with organic material Poly‐Imide (PI) film. Moving path of the accumulated charge by one polarity electrode is formed through PI film and the Image‐Sticking level has been reduced.